PENGARUH KOMPENSASI RUGI FISKAL DAN PAJAK TANGGUHAN TERHADAP PENGHINDARAN PAJAK PADA PERUSAHAAN SUB SEKTOR MINYAK DAN GAS BUMI YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2017-2020 - Pebrianto Girsang; Remista Simbolon (Jurnal Ekonomis, 2021)
This study was conducted to examine and determine the effect of tax loss compensation and deferred tax on tax avoidance. The population used for this study were 13 oil and gas sub-sector companies listed on the Indonesia Stock Exchange (IDX) for the 2017-2020 period, and the sample was only 10 Companies that met the criteria of the researcher who reported their commercial reports for four consecutive years. Participate (2017-2020), so the total sample is 40 data. The method used in this study is to use quantitative methods, by conducting descriptive analysis, Classical assumption test, normality test, correlation coefficient test, hypothesis testing, coefficient of determination test, simple regression test, F-simultaneous test, multiple regression with a significance level of approx. 0.05 (5%). The results of this study indicate the significance value of Fiscal Loss Compensation (X1) 0.157 > 0.05 which means it has no effect on Tax Avoidance (Y). The significance value of Deferred Tax (X2) is 0.116 > 0.05 which means it has no effect on Tax Avoidance (Y). Simultaneously the two independent variables are 0.192 which means > 0.05. So there is no significant effect between Fiscal Loss Compensation (X1) and Deferred Tax (X2) on Tax Avoidance (Y)